Estimation of the Inflation Threshold in the Libyan Economy During the Period 1990–2024: An Econometric Study Using a Dynamic Threshold Model and Bootstrap Tests (Al-Farooq Journal of Sciences, 2026)
This study tests whether the inflation–growth relationship in Libya is nonlinear over 1990–2024 and whether a statistically defensible inflation threshold can be identified. Annual data on real GDP growth, CPI inflation, gross fixed capital formation as a share of GDP, oil-production growth, a 2011 pulse dummy, and lagged growth are used in a continuous piecewise dynamic regression. Candidate thresholds are searched after 15% trimming and linearity is tested with a Sup-F statistic and wild bootstrap inference. The residual sum of squares is minimized at an inflation rate of about 10.40%. The estimated inflation slope is 0.216 below that candidate point and -0.289 above it. However, the observed Sup-F statistic is only 0.485 and the bootstrap p-value is about 0.702, so linearity cannot be rejected. The linear specification also performs slightly better according to AIC and BIC. Robustness exercises using alternative controls, samples, and non-hydrocarbon growth produce candidate thresholds between about 6.25% and 10.40%, but none is statistically significant. The main conclusion is therefore not that Libya has a 10.40% inflation threshold, but that the available annual data do not establish a stable inflation threshold for 1990–2024. Oil-sector shocks, structural breaks, the small sample, and measurement limitations are central to interpreting this result.
Keywords: Libya, inflation, economic growth, inflation threshold, threshold regression, bootstrap, oil production.